Comparative Media History : an introduction : 1789 to the present - Chapman, Jane, 1950- (UK : Polity Press, 2005)
"Comparative Media History is a thematic textbook which introduces students to the key ideas underpinning media development. It is an essential first step to a better understanding of both the media industry today and the way in which it evolved over time." "The textbook compares developments and influences from a broad perspective, highlighting and contrasting different countries, industries and periods of history in order to encourage an understanding of cause and effect."--Jacket
1. Newspapers : radicalism, repression and economic change, 1789-1847 -- 2. Focusing of political communications and the newspaper business, 1848-1881 -- 3. Commercialization, consumerism and technology -- 4. Politics, new forms of communication and the globalizing process -- 5. Business and ideology of mass culture, 1918-1939 -- 6. War and beyond, 1939-1947 -- 7. Cold War and the victory of commercialism, 1948-1980 -- 8. Continuity and change since 1980
Includes bibliographical references (p. 269-284) and index.
Keywords: Mass media -- History